Податкове планування в умовах соціальної відповідальності бізнесу - Глущенко, Я.І. (Культура народов Причерноморья, 2013)
У статті розглядається взаємозв’язок соціальної відповідальності бізнесу і процесу
податкового планування підприємства. Досліджено положення податкового законодавства, які
можуть бути враховані при розробці податкового стратегії підприємства та вплинути на підвищення
репутації, появи конкурентних переваг суб’єкта господарювання в галузі. Визначено своєчасність
сплати податків, як один з аспектів реалізації соціальної відповідальності суб’єктів господарювання
перед суспільством. В статье рассмотрена взаимосвязь социальной ответственности бизнеса и процесса
налогового планирования предприятия. Исследованы положения налогового законодательства, которые
могут быть учтены при разработке налоговой стратегии предприятия, приводящие к улучшению
репутации, появлению конкурентных преимуществ субъекта хозяйствования в отрасли.
Своевременность уплаты налогов определена как аспект реализации социальной ответственности
субъектов хозяйствования перед обществом. The article studies the interrelations of social responsibility of business and the process of enterprise
tax planning. The author researched the provisions of the tax legislation which are to be taken into account
within the process of enterprise tax strategy development and may influence upon reputation consolidation and
emerging competitive advantages of the business entities within industry branch. Thus the increasing the general
societal reputation of the enterprise may be promoted by the charity activity. At the same time undertaking
charity and similar payments and value of goods (works, services) for nonprofit organizations, money transfers
to all Ukrainian union of people who acquired some damages due to Chernobyl catastrophe, the amounts of
cash or property values which are willingly transfer for the purposeful utilization targeted at protection of
cultural heritage to the establishments of science, education, culture, national parks, museums are to be included
into the set of costs which are accounted while calculation taxed incomes.
Competitive advantages of the goods produced are connected with increasing labour productivity which depends
on professional level and educational backgrounds and psychological factors of motivation which are reflected
in care of employees. According to the norms of tax code of Ukraine the following is to be included into the set
of costs which are to be accounted while calculating taxed incomes: costs of education and vocational training,
retraining or qualification upgrade at the national or foreign educational establishments physical persons; costs
of long term insurance of workers at the account of enterprise financial means.
The article gives ground for the fact that paging taxes in good time is one of the aspects of realization of the
industrial entity’s social responsibility within society.
Notwithstanding the fact that Ukrainian tax system doesn’t acquire unique conception of social targeting of tax
system, development the process of taxation planning at the microlevel is to include procedures which could take
into account definite provisions of the tax legislation which enable businesses to improve the image of the
enterprise as well as its business reputation within the frameworks of the social responsibilities of business
program realization.